Electrolytic capacitors

By using the first polymer with an acid group in the cathode extraction layer of the electrolytic capacitor to bond with the carbon material, the problem of poor ESR rise suppression effect in the high temperature environment in the prior art is solved, and a more effective ESR suppression effect is achieved.

CN114207754BActive Publication Date: 2025-04-04PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080055189.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-08
Filing Date
2020-07-31
Publication Date
2025-04-04
Estimated Expiration
2040-07-31

AI Technical Summary

Technical Problem

The existing electrolytic capacitors have insufficient effect on suppressing the rise of ESR in high temperature environments, especially in high temperature environments.

Method used

The first polymer having an acid group is introduced into the cathode extraction layer of the electrolytic capacitor, and is bonded to the carbon material to improve the gas barrier and adhesion of the carbon layer, reduce the transmission of air, and suppress the rise of the resistance of the solid electrolyte layer.

Benefits of technology

By improving the adhesion between the carbon layer and the solid electrolyte layer, the rise of ESR is effectively suppressed, and the high ESR suppression effect can be maintained especially in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114207754B_ABST
    Figure CN114207754B_ABST
Patent Text Reader

Abstract

The electrolytic capacitor includes a capacitor element, which includes an anode body, a dielectric layer covering at least a portion of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a cathode lead layer covering at least a portion of the solid electrolyte layer. The cathode lead layer includes a carbon material and a first polymer having an acid group. The acid group includes at least one selected from a sulfonic group, a carboxyl group, and derivatives thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to electrolytic capacitors. Background Art

[0002] An electrolytic capacitor includes a capacitor element and an outer casing covering the capacitor element. As an example of an electrolytic capacitor, there is a solid electrolytic capacitor using a conductive polymer or the like as a solid electrolyte. In this case, the capacitor element includes an anode body, a dielectric layer formed on the anode body, a solid electrolyte layer formed on the dielectric layer, and a cathode lead layer formed on the solid electrolyte layer. The cathode lead layer is electrically connected to a cathode lead terminal.

[0003] As a structure of the cathode lead layer, for example, Patent Document 1 proposes adding an aromatic compound having a sulfonic acid group to a carbon layer to improve adhesion between a solid electrolyte layer containing a conductive polymer and the carbon layer and reduce the equivalent series resistance (ESR) of the electrolytic capacitor.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2008-27998 Summary of the invention

[0007] However, the electrolytic capacitor of Patent Document 1 cannot be said to have a sufficient effect of improving ESR (particularly, an effect of suppressing an increase in ESR in a high-temperature environment), and further improvement is desired.

[0008] One aspect of the present invention relates to an electrolytic capacitor comprising a capacitor element, the capacitor element having an anode body, a dielectric layer covering at least a portion of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a cathode lead layer covering at least a portion of the solid electrolyte layer, the cathode lead layer comprising a carbon material and a first polymer having an acid group, the acid group comprising at least one selected from a sulfonic group, a carboxyl group, and derivatives thereof.

[0009] It is possible to suppress an increase in the ESR of an electrolytic capacitor including a solid electrolyte layer.

[0010] BRIEF DESCRIPTION OF THE DRAWINGS

[0011] [ Figure 1 ] Figure 1 This is a cross-sectional view schematically showing an electrolytic capacitor according to one embodiment of the present invention. DETAILED DESCRIPTION

[0012] [Electrolytic capacitors]

[0013] An electrolytic capacitor according to one embodiment of the present invention includes a capacitor element, the capacitor element having an anode body, a dielectric layer covering at least a portion of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a cathode lead layer covering at least a portion of the solid electrolyte layer. The cathode lead layer includes a carbon material and a first polymer having an acid group. The acid group includes at least one selected from a sulfonic group, a carboxyl group, and derivatives thereof.

[0014] For electrolytic capacitors with solid electrolyte layers, the capacitor element is usually covered by a resin outer casing, but air (especially oxygen, or oxygen and moisture) can easily penetrate the outer casing and penetrate into the interior. If the air that penetrates into the electrolytic capacitor contacts the solid electrolyte layer, the conductive polymer contained in the solid electrolyte layer may deteriorate.

[0015] In the capacitor element, at least a portion of the solid electrolyte layer is covered by the cathode lead layer. The cathode lead layer usually includes a carbon layer. However, the carbon layer is usually in a state of being assembled from granular carbon materials, so the film quality cannot be said to be dense. Therefore, if air invades the electrolytic capacitor, it is easy to penetrate the carbon layer, and the air that penetrates the carbon layer contacts the solid electrolyte layer, which sometimes degrades the conductive polymer contained in the solid electrolyte layer. Such degradation of conductive polymers becomes particularly significant under high temperature and / or high humidity. If the conductive polymer degrades, the resistance of the solid electrolyte layer increases, and the ESR of the electrolytic capacitor rises.

[0016] For the electrolytic capacitor of the present embodiment, in the capacitor element, the carbon layer contained in the cathode lead layer covering at least a portion of the solid electrolyte layer contains, in addition to the carbon material, a first polymer having an acid group. The conductive polymer has a functional group (for example, -S- or -NH-, etc.) that is easily positively charged, and the acid group of the first polymer can be bonded to these functional groups of the conductive polymer. On the other hand, the polymer chain of the first polymer is entangled with the carbon particles, so that the first polymer can be firmly adhered to the carbon material. Therefore, the adhesion between the carbon material and the conductive polymer can be improved through the first polymer. As a result, the gas barrier properties of the carbon layer are improved, and the permeation of air is reduced. As a result, the increase in the resistance of the solid electrolyte layer is suppressed, and the increase in the ESR in the electrolytic capacitor can be suppressed.

[0017] In addition, the first polymer is more thermally stable than its monomer, so it is easy to maintain high adhesion between the carbon material and the conductive polymer even in a high temperature environment. Therefore, by including the first polymer, a high suppression effect of ESR increase can be obtained even at high temperatures.

[0018] The acid group is, for example, a sulfo group (-SO3H) or a carboxyl group (-COOH), and is introduced into the monomer corresponding to the repeating unit of the first macromolecule. The acid group may also be a derivative of a sulfo group and / or a carboxyl group. The derivative of a sulfo group and / or a carboxyl group includes an anionic group obtained by dissociating a proton from a sulfo group and / or a carboxyl group, and a salt of an anionic group and a cation (e.g., a sodium salt, etc.). The derivative may also be an ester of an acid group and an alcohol.

[0019] In addition to the first polymer, the second polymer may also be included in the cathode lead-out layer. The second polymer can synergistically improve the ESR rise suppression effect or give the second polymer other functions. The second polymer may have an acid group like the first polymer, or may not have an acid group. The second polymer may be water-soluble, for example. Water-soluble polymers generally have polar groups that can be densely oriented through hydrogen bonds. Therefore, there is little space in the polymer for the diffusion of gases such as oxygen, and it is difficult for gases to penetrate the polymer. Therefore, the second polymer can improve the oxygen barrier. As a result, the oxidative degradation of the conductive polymer is suppressed, thereby further suppressing the rise in ESR.

[0020] Among water-soluble polymers, cellulose polymers and polyvinyl alcohol have high oxygen barrier properties and can be preferably used as the second polymer. It should be noted that cellulose polymers include cellulose ethers and cellulose esters, and can include, for example, carboxymethyl cellulose or hydroxyethyl cellulose, derivatives obtained by chemically modifying the hydroxyl group of glucose, a monomer constituting cellulose. In addition, the derivatives of cellulose polymers can have a high-order structure, and can particularly include a fibril structure.

[0021] The cathode lead layer may be a two-layer structure of a first conductive layer covering at least a portion of the solid electrolyte layer and a second conductive layer covering at least a portion of the first conductive layer. In this case, the first polymer may be at least contained in the first conductive layer. The adhesion between the solid electrolyte layer and the first conductive layer is improved, and the increase in ESR can be suppressed. For example, the first conductive layer is a carbon layer, and the second conductive layer is a silver paste layer.

[0022] Hereinafter, the configuration of the electrolytic capacitor will be described in more detail with reference to the drawings as appropriate. Figure 1 1 is a cross-sectional view schematically showing the structure of an electrolytic capacitor according to an embodiment of the present invention. In the illustrated example, the electrolytic capacitor 1 includes: a capacitor element 2; a resin outer casing 3 that seals the capacitor element 2; and an anode lead terminal 4 and a cathode lead terminal 5, at least a portion of which is exposed to the outside of the outer casing 3. The outer casing 3 has a substantially rectangular parallelepiped shape, and the electrolytic capacitor 1 also has a substantially rectangular parallelepiped shape.

[0023] Capacitor element 2 includes anode body 6 constituting an anode portion, dielectric layer 7 covering anode body 6 , and cathode portion 8 covering dielectric layer 7 .

[0024] The anode body 6 includes a region facing the cathode portion 8 and a region not facing the cathode portion 8. Of the region of the anode body 6 not facing the cathode portion 8, an insulating separation layer 13 is formed in a portion adjacent to the cathode portion 8, and the contact between the cathode portion 8 and the anode body 6 is limited. The insulating separation layer 13 covers the surface of the anode body 6 in a strip-like manner, for example. Of the region of the anode body 6 not facing the cathode portion 8, another portion is electrically connected to the anode lead terminal 4 by welding. The cathode lead terminal 5 is electrically connected to the cathode portion 8 via an adhesive layer 14 formed by a conductive adhesive.

[0025] The cathode portion 8 includes a solid electrolyte layer 9 covering the dielectric layer 7, and a cathode lead layer 10 covering the solid electrolyte layer 9. The cathode lead layer 10 includes a carbon layer 11 (first conductive layer) and a silver paste layer 12 (second conductive layer). Here, the carbon layer 11 includes a carbon material and a first polymer. Since the carbon layer 11 includes the first polymer, the adhesion between the carbon layer 11 and the solid electrolyte layer 9 is improved, so that even if air intrudes into the interior of the outer casing 3, the contact between the solid electrolyte layer 9 and the air can be suppressed. Therefore, the degradation of the conductive polymer contained in the solid electrolyte layer 9 is suppressed.

[0026] Hereinafter, the structure of the electrolytic capacitor will be described in more detail.

[0027] (Capacitor element 2)

[0028] Capacitor element 2 includes anode body 6 constituting an anode portion, dielectric layer 7, and cathode portion 8 including solid electrolyte layer 9. Cathode portion 8 includes solid electrolyte layer 9 and cathode extraction layer 10 covering solid electrolyte layer 9.

[0029] The electrolytic capacitor only needs to have at least one capacitor element 2, and may have one capacitor element 2 or may have a plurality of capacitor elements. The number of capacitor elements included in the electrolytic capacitor may be determined according to the application.

[0030] (Anode 6)

[0031] The anode body 6 may include: a valve metal, an alloy containing a valve metal, a compound containing a valve metal, and the like. These materials may be used alone or in combination of two or more. As the valve metal, for example, aluminum, tantalum, niobium, and titanium are preferably used. The anode body 6 having a porous surface is obtained, for example, by roughening the surface of a valve metal-containing substrate (a foil-shaped or plate-shaped substrate, etc.) by etching or the like. In addition, the anode body 6 may be a formed body of particles containing a valve metal or a sintered body thereof. It should be noted that the sintered body has a porous structure. That is, in the case where the anode body 6 is a sintered body, the entire anode body 6 may be porous.

[0032] (Dielectric layer 7)

[0033] The dielectric layer 7 is formed by anodizing the valve metal on the surface of the anode body 6 by chemical conversion treatment or the like. The dielectric layer 7 may be formed so as to cover at least a portion of the anode body 6. The dielectric layer 7 is usually formed on the surface of the anode body 6. Since the dielectric layer 7 is formed on the porous surface of the anode body 6, it is formed along the inner wall surface of the pores and depressions (pits) on the surface of the anode body 6.

[0034] The dielectric layer 7 includes an oxide of a valve metal. For example, when tantalum is used as the valve metal, the dielectric layer includes Ta2O5, and when aluminum is used as the valve metal, the dielectric layer includes Al2O3. It should be noted that the dielectric layer 7 is not limited thereto, and any material that functions as a dielectric may be used. When the surface of the anode body 6 is porous, the dielectric layer 7 is formed along the surface of the anode body 6 (including the inner wall surface of the pores).

[0035] (Cathode portion 8)

[0036] (Solid Electrolyte Layer 9)

[0037] The solid electrolyte layer 9 constituting the cathode portion 8 includes a conductive polymer and may further include a dopant, an additive, etc. as required. As the conductive polymer, for example, polypyrrole, polythiophene, polyaniline, polyacetylene, polyphenylene, polyphenylene vinylene, polyacene, and / or polythiophene vinylene, and derivatives thereof may be used. The solid electrolyte layer 9 may be formed, for example, by chemically polymerizing and / or electrolytically polymerizing the raw material monomers on the dielectric layer 7. Alternatively, it may be formed by contacting a solution in which a conductive polymer is dissolved or a dispersion in which a conductive polymer is dispersed with the dielectric layer 7. The solid electrolyte layer 9 may be formed in a manner that covers at least a portion of the dielectric layer 7.

[0038] (Cathode extraction layer 10)

[0039] Cathode lead layer 10 constituting cathode portion 8 includes carbon layer 11 and silver paste layer 12 . Cathode lead layer 10 is formed so as to cover at least a portion of solid electrolyte layer 9 .

[0040] (Carbon layer 11)

[0041] The carbon layer 11 (first conductive layer) contains a carbon material and a first polymer and has conductivity. The carbon layer 11 may contain a binder and / or an additive as necessary.

[0042] As the carbon material, conductive carbon particles are preferred. As carbon particles, for example, graphite, graphene, carbon black, soft carbon, hard carbon, etc. can be cited. As graphite, a material with a graphite-type crystal structure can be used, and any one of artificial graphite and natural graphite can also be used. As carbon particles, carbon nanotubes, carbon fibers, etc. can be used. Carbon particles can also be materials obtained by cutting fibrous carbon materials such as carbon nanotubes and carbon fibers into appropriate lengths (also including crushed materials, etc.). These carbon particles can be used alone or in combination of two or more.

[0043] The carbon particles preferably include flaky particles. In this case, in the carbon layer 11, the carbon particles are easily filled in an overlapping layered state. The first polymer can be between the overlapping flaky particles. As a result, the carbon layer 11 is in close contact with the solid electrolyte layer 9, and air is difficult to invade. Therefore, the degradation of the conductive polymer contained in the solid electrolyte layer 9 is suppressed. If it is a flaky form, the type of carbon material constituting the particles is not particularly limited, but graphite, graphene, etc. are easy to obtain a flaky form, and it is easy to obtain flaky particles.

[0044] The average aspect ratio of the carbon particles is, for example, 1.5 or more, preferably 2 or more. When the average aspect ratio of the carbon particles is within such a range, many flat particles such as flaky particles are included. Therefore, the carbon particles are easily filled in an overlapping state in the carbon layer 11. Therefore, the densely formed carbon layer can further improve the air permeation suppression effect in the carbon layer 11.

[0045] It should be noted that the average aspect ratio of the carbon particles can be obtained as follows from an electron microscope photograph of a cross section of the carbon layer 11. First, select any plurality of (e.g., 10) carbon particles, and measure the maximum diameter D1 and the maximum diameter D2 in a direction orthogonal to the maximum diameter D1 for each carbon particle. Then, divide D1 by D2 to obtain the aspect ratio of each particle, and then average them to calculate the average aspect ratio.

[0046] The average particle size of the carbon particles is, for example, 0.05 μm or more, preferably 0.1 μm or more. When the average particle size is within such a range, it is easy to densely fill the carbon particles in the carbon layer 11, and it is easy to ensure high conductivity. The average particle size of the carbon particles is preferably 10 μm or less, and more preferably 5 μm or less. In this case, it is easy to fill the gaps between the carbon particles with silver, so that the air permeation suppression effect in the carbon layer 11 can be further improved.

[0047] The average particle size of the carbon particles can be obtained by selecting any number of (e.g., 10) carbon particles in an electron micrograph of a cross section of the carbon layer 11, measuring the particle size of each carbon particle, and averaging the particle size. The diameter of a circle having the same area as the cross-sectional area of ​​the carbon particles observed in the electron micrograph is set as the particle size of the carbon particles.

[0048] In addition to the carbon material, the carbon layer 11 also includes a first polymer having an acid group. The conductive polymer contained in the solid electrolyte layer 9 is easily positively charged by hole doping. Specifically, for example, the -NH- group or -N= group contained in polypyrrole or polyaniline, or the -S- group contained in polythiophene is easily converted into -NH2 + -yl, -NH + = base, or -S + = group. The acid group of the first polymer is bonded to these positively charged functional groups, so that the first polymer can be closely attached to the conductive polymer. On the other hand, the polymer chain of the first polymer is attached to the surface of the carbon particles in a tangled manner, so that the first polymer can be closely attached to the carbon particles. As a result, the adhesion between the carbon particles and the conductive polymer is improved by the intervention of the first polymer. Therefore, the permeation of air from the carbon layer 11 to the solid electrolyte layer 9 is reduced, and the increase in resistance caused by the deterioration of the conductive polymer (that is, the increase in the ESR of the electrolytic capacitor) can be suppressed.

[0049] In the first polymer, the acid group can be a sulfonic group (-SO3H), a carboxyl group (-COOH) or a derivative thereof. The derivative includes an anionic group obtained by dissociating a proton from the acid group, a salt of an anionic group and a cation, and an ester obtained by reacting an acid group with an alcohol. The acid group is introduced into a monomer corresponding to the repeating unit of the first polymer. The number of acid groups contained in the first polymer can be more than 50, or more than 85, relative to 100 monomers.

[0050] The content of the first polymer can be 1 mass part or more, 2 mass parts or more, 5 mass parts or more, or 10 mass parts or more relative to 100 mass parts of carbon material. By including 1 mass part or more of the first polymer relative to 100 mass parts of carbon material, the adhesion between the cathode lead layer (carbon layer) and the solid electrolyte layer is improved, and the increase in the ESR of the electrolytic capacitor can be suppressed. On the other hand, if the content of the first polymer is too large, the viscosity of the carbon paste used to form the carbon layer increases. In addition, there is a situation where the resistance of the carbon layer becomes large and the effect of suppressing the increase of ESR is offset. Therefore, in order not to impair the operability of the carbon paste coating and not to offset the effect of suppressing the increase of ESR, the content of the first polymer is set to 5000 mass parts or less relative to 100 mass parts of carbon material. The content of the first polymer can be 1000 mass parts or less, or 100 mass parts or less relative to 100 mass parts of carbon material.

[0051] The content of the first polymer may be 1 to 5000 parts by mass, 2 to 1000 parts by mass, 5 to 100 parts by mass, or 10 to 100 parts by mass relative to 100 parts by mass of the carbon material.

[0052] The weight average molecular weight of the first polymer is, for example, in the range of 2,000 to 1,000,000. By using the first polymer having a weight average molecular weight in this range, the carbon layer 11 and the solid electrolyte layer 9 are closely attached, the air permeation from the carbon layer 11 to the solid electrolyte layer 9 is reduced, and the increase of ESR can be suppressed.

[0053] The first polymer may be a resin material.

[0054] Regarding the first polymer, for example, as an example having a sulfonic group, any one of a polymer having an aromatic sulfonic acid in a monomer structure and a polymer having an aliphatic sulfonic acid in a monomer structure can be used. As a polymer having an aromatic sulfonic acid in a monomer structure, polystyrene sulfonic acid, phenolsulfonic acid novolac resin, etc. can be cited. As a polymer having an aliphatic sulfonic acid in a monomer structure, polyvinyl sulfonic acid, polyallyl sulfonic acid, etc. can be cited. In addition, as an example of the first polymer having a carboxyl group (or its derivative), acrylic resins such as polyacrylic acid, polymethacrylic acid, polymethyl acrylate, polymethyl methacrylate, or polyethylene terephthalate, etc. can be cited.

[0055] As the first polymer, poly(ethyl acrylate sulfonic acid), poly(butyl acrylate sulfonic acid), poly(methacrylic acid sulfonic acid), poly-2-acrylamide-2-methylpropane sulfonic acid, etc. may also be used.

[0056] In addition to the first polymer, the second polymer may also be included in the carbon layer. The second polymer may be water-soluble. The water-soluble second polymer is easily bonded to another second polymer or the first polymer through hydrogen bonds, and is easily formed into a compact structure through hydrogen bonds within the molecular chain. Therefore, there is less space in the polymer for diffusion of gases such as oxygen, and it is difficult for gases to penetrate the polymer. Therefore, the use of the second polymer can improve oxygen barrier properties. As a result, the oxidative degradation of the conductive polymer is suppressed, thereby further suppressing the increase in the ESR of the electrolytic capacitor.

[0057] Examples of the second polymer having excellent oxygen barrier properties include cellulose-based polymers and / or polyvinyl alcohol.

[0058] Derivatives of cellulose-based polymers include those with higher order structures, particularly fibril structures. The use of fibrillated cellulose is preferred because it not only improves oxygen barrier properties but also imparts thixotropy, thereby stabilizing the carbon layer formed by the carbon paste after coating.

[0059] The weight average molecular weight of the second polymer is, for example, in the range of 2,000 to 1,000,000. The content of the second polymer is not limited, but for example, in consideration of workability, it can be 10 parts by mass or less relative to 100 parts by mass of the carbon material. Similar to the first polymer, the second polymer can have an acid group. The content of the second polymer can be 5 to 50 parts by mass, 5 to 35 parts by mass, 8 to 35 parts by mass, or 8 to 32 parts by mass relative to 100 parts by mass of the first polymer.

[0060] As the binder and additive contained in the carbon layer 11, known components used in the carbon layer of the electrolytic capacitor can be used without particular limitation. The carbon layer 11 may contain a metal element such as silver.

[0061] The average thickness of the carbon layer 11 is, for example, 0.01 μm to 50 μm. The average thickness is obtained, for example, by measuring the thickness of a plurality of locations (for example, 10 locations) of the carbon layer 11 in an electron microscope photograph of a cross section of the carbon layer 11 and averaging the thicknesses.

[0062] (Silver paste layer 12)

[0063] The silver paste layer 12 (second conductive layer) contains, for example, silver particles and a binder. The silver paste layer 12 may contain additives and the like as necessary. Examples of the additives include known additives used for silver paste layers.

[0064] The silver particles may contain other metal elements. The content of other metal elements in the silver particles is preferably 0.1 mass % or less.

[0065] The silver content in silver paste layer 12 is, for example, greater than 50 mass %, preferably 70 mass % or more. When the silver content is within this range, high conductivity of silver paste layer 12 is ensured, thereby improving current collection from capacitor element 2 .

[0066] The silver paste layer 12 may contain the above-mentioned first polymer and / or second polymer.

[0067] The binder contained in the silver paste layer 12 is not particularly limited, but a cured product of a curable resin is preferred. Examples of the curable resin include thermosetting resins such as epoxy resins.

[0068] (Exterior body 3)

[0069] External package 3 covers capacitor element 2. Usually, part of lead terminals 4 and 5 are also covered by external package 3. External package 3 is formed by sealing capacitor element 2 and part of lead terminals 4 and 5 with a resin material.

[0070] The outer casing 3 preferably contains a cured product of a curable resin composition, and may contain a thermoplastic resin or a composition containing the thermoplastic resin. As the curable resin composition and the thermoplastic resin (composition), those exemplified below can be used.

[0071] For the outer casing 3 formed of a resin material, the resin material is easily degraded or easily damaged by mechanical impact, and the external air easily penetrates the outer casing 3 and intrudes into the outer casing. According to the present embodiment, by including the first polymer, the adhesion of the cathode lead layer (carbon layer) is improved, so the gas barrier property of the cathode lead layer is high, and even when using the outer casing 3 formed of a resin material, the contact between the solid electrolyte layer 9 and the air can be suppressed (or reduced).

[0072] (Lead terminals 4, 5)

[0073] One end of the lead terminal 4, 5 is electrically connected to the capacitor element 2, and the other end is led out to the outside of the outer casing 3. In the electrolytic capacitor 1, one end side of the lead terminal 4, 5 is covered by the outer casing 3 together with the capacitor element 2. As the lead terminal 4, 5, the lead terminal used in the electrolytic capacitor can be used without particular limitation, and for example, those called lead frames can be used. As the raw material of the lead terminal 4, 5, for example, metals such as copper or alloys thereof can be cited.

[0074] [Method for manufacturing electrolytic capacitor]

[0075] The above-mentioned electrolytic capacitor is manufactured by a manufacturing method having the following steps: a step of forming a dielectric layer in a manner covering at least a portion of the anode body, a step of forming a solid electrolyte layer in a manner covering at least a portion of the dielectric layer, and a step of forming a cathode lead layer on at least a portion of the solid electrolyte layer. The step of forming the cathode lead layer includes, for example, a step of forming a carbon layer, and a step of forming a silver paste layer on at least a portion of the carbon layer. The manufacturing method of the electrolytic capacitor may further include a step of preparing the anode body before the step of forming the dielectric layer. In addition, the manufacturing method of the electrolytic capacitor may further include a step of electrically connecting the lead terminal to the capacitor element, and a step of covering the capacitor element and a portion of the lead terminal with an outer body (sealing step).

[0076] Hereinafter, each step will be described in more detail.

[0077] (Step of Preparing Anode Body 6)

[0078] In this step, anode body 6 constituting the anode portion is formed by a known method depending on the type of anode body 6 .

[0079] Anode body 6 can be prepared, for example, by roughening the surface of a foil or plate-shaped substrate containing a valve metal. Roughening can be performed by forming irregularities on the substrate surface, for example, by etching the substrate surface (for example, electrolytic etching).

[0080] In addition, without limitation to the above, the valve-acting metal powder may be molded into a desired shape (for example, a block shape) to obtain a molded body, and the molded body may be sintered to form the anode body 6 having a porous structure.

[0081] (Step of Forming Dielectric Layer 7)

[0082] In this process, a dielectric layer 7 is formed on the anode body 6. The dielectric layer 7 is formed by anodizing the anode body 6. Anodization can be performed by a known method, such as a chemical conversion treatment. The chemical conversion treatment can be performed, for example, by immersing the anode body 6 in a chemical conversion solution so that the chemical conversion solution is infiltrated into the surface of the anode body 6, and using the anode body 6 as an anode, applying a voltage between the anode body 6 and a cathode immersed in the chemical conversion solution. As the chemical conversion solution, for example, a phosphoric acid aqueous solution is preferably used.

[0083] (Step of Forming Solid Electrolyte Layer 9)

[0084] In this process, a solid electrolyte layer 9 is formed on the dielectric layer 7. For example, a treatment liquid containing a conductive polymer is attached to the anode body 6 on which the dielectric layer 7 is formed, and then dried to form the solid electrolyte layer 9. The treatment liquid may also contain other components such as a dopant. For example, poly(3,4-ethylenedioxythiophene) (PEDOT) is used as the conductive polymer. For example, polystyrene sulfonic acid (PSS) is used as the dopant. The treatment liquid is, for example, a dispersion or solution of a conductive polymer. As a dispersion medium (solvent), for example, water, an organic solvent, or a mixture thereof can be cited. The solid electrolyte layer 9 can be formed by chemically polymerizing and / or electrolytically polymerizing the raw material monomers of the conductive polymer on the dielectric layer 7.

[0085] (Step of Forming Cathode Leading Layer 10)

[0086] In this step, the carbon layer 11 and the silver paste layer 12 are sequentially stacked on the solid electrolyte layer 9 to form the cathode lead layer 10 .

[0087] (Step of Forming Carbon Layer 11)

[0088] In this step, the carbon paste is attached to at least a portion of solid electrolyte layer 9 to form carbon layer 11. Carbon layer 11 can be formed by further heating the coating film of the carbon paste formed on at least a portion of solid electrolyte layer 9.

[0089] The carbon paste contains a carbon material, a first polymer, and a dispersion medium. As the dispersion medium, water, an organic medium, or a mixture thereof is used. The carbon paste may contain a binder and / or an additive as required. The carbon paste may also contain a second polymer.

[0090] Examples of the carbon material contained in the carbon paste include those described for the carbon layer 11. The carbon material preferably includes flaky carbon particles. The average aspect ratio and average particle size of the carbon particles can be selected from the ranges described for the carbon layer 11. Similarly, examples of the first and second polymers include those described for the carbon layer 11.

[0091] It should be noted that the average aspect ratio and average particle size of the carbon particles are those measured for the carbon particles used for the carbon paste. In addition to being obtained from an electron microscope photograph of the carbon particles, the average aspect ratio of the carbon particles can also be calculated in the same manner as the average aspect ratio of the carbon particles contained in the carbon layer 11. The average particle size of the carbon particles is the 50% particle size D50 (i.e., median particle size) in the volume-based particle size distribution obtained using a particle size distribution measuring device using a laser diffraction scattering method.

[0092] The binder contained in the carbon paste is not particularly limited, and examples thereof include known binders used for preparing carbon layers. As the binder, for example, a polymer binder such as a thermoplastic resin (polyester resin, etc.) or a thermosetting resin (polyimide resin, epoxy resin, etc.) is preferred.

[0093] The additive is not particularly limited, and examples thereof include known additives used for the preparation of carbon layers. Examples of the additive include dispersants, surfactants, antioxidants, preservatives, alkalis, and / or acids.

[0094] The carbon layer 11 can be formed by attaching a carbon paste to at least a portion of the solid electrolyte layer 9 to form a coating film, and then drying the coating film. After the coating film is formed, heating may be further performed.

[0095] The carbon paste may be brought into contact with solid electrolyte layer 9 . For example, anode body 6 including solid electrolyte layer 9 may be immersed in the carbon paste, or the carbon paste may be applied to the surface of solid electrolyte layer 9 using a known coater or the like.

[0096] The temperature for heating the coating film of the carbon paste is, for example, 150° C. or higher and 300° C. or lower.

[0097] (Step of Forming Silver Paste Layer 12)

[0098] In this process, a silver paste layer 12 is formed on at least a portion of the carbon layer 11. The silver paste layer 12 can be formed by attaching a silver paste to at least a portion of the carbon layer 11. The silver paste can contain silver particles, a binder, a dispersion medium, and additives as required. As for the silver particles, the binder, and the additives, reference can be made to the description of the silver paste layer 12. The silver paste can contain a first polymer and / or a second polymer. As for the dispersion medium, water, an organic medium, and a mixture thereof can be cited.

[0099] The silver paste layer 12 can be formed by drying and / or heating a coating of silver paste formed on at least a portion of the carbon layer 11. For example, when a thermosetting resin is used as the binder, the silver paste layer 12 is formed by heating the coating of the silver paste to cure the binder.

[0100] (Lead terminal connection process)

[0101] In this process, the anode lead terminal 4 and the cathode lead terminal 5 are electrically connected to the capacitor element 2. The connection of each lead terminal can be performed after the capacitor element 2 is manufactured. The connection of the cathode lead terminal 5 to the capacitor element 2 is performed after the capacitor element 2 is manufactured, but the connection of the anode lead terminal 4 to the anode body 6 can be performed at an appropriate stage of the process of manufacturing the capacitor element 2. For example, in the case of forming an anode body with a porous structure by sintering, a molded body formed into a desired shape is obtained in a state where one end of the anode lead terminal in the long side direction of a rod-shaped body is buried in the powder of the valve-acting metal. Then, by sintering this molded body, a porous anode body with one end of the anode lead terminal buried can be formed.

[0102] When a stack of multiple capacitor elements is used, anode lead terminal 4 may be connected to anode body 6 in the same manner as described above. Cathode lead terminal 5 may be connected to the capacitor element in the same manner as described above, or one end of cathode lead terminal 5 may be connected to a stack of multiple capacitor elements whose cathode portions 8 are electrically connected to each other.

[0103] (Sealing process)

[0104] In this step, capacitor element 2 and a portion of lead terminals 4 and 5 are covered with outer package 3, thereby sealing capacitor element 2 with outer package 3. More specifically, after capacitor element 2 and lead terminals 4 and 5 are electrically connected, capacitor element 2 and a portion of lead terminals 4 and 5 can be sealed by covering them with a resin constituting the resin outer package.

[0105] The outer casing 3 can be formed using a molding technique such as injection molding, insert molding, and compression molding. The outer casing 3 can be formed, for example, by using a predetermined mold and filling a curable resin composition or a thermoplastic resin (composition) in a predetermined position in a manner covering the capacitor element 2 and one end of the lead terminals 4 and 5. In the case of a laminate of multiple capacitor elements, the resin outer casing can be formed in a manner covering a portion of the laminate and the lead terminals.

[0106] In addition to the curable resin, the curable resin composition may further include a filler, a curing agent, a polymerization initiator, and / or a catalyst, etc. As the curable resin, for example, epoxy resins, phenol resins, urea resins, polyimides, polyamide-imides, polyurethanes, diallyl phthalate, unsaturated polyesters, etc. The curable resin composition may also include a plurality of curable resins.

[0107] As fillers, for example, insulating particles (inorganic, organic) and / or fibers are preferred. As insulating materials constituting the fillers, for example, insulating compounds (oxides, etc.) such as silica and alumina, glass, mineral materials (talc, mica, clay, etc.) and the like can be cited. The resin casing may contain one of these fillers, or a combination of two or more of these fillers. The content of the filler in the resin casing is, for example, 10 to 90% by mass.

[0108] As the thermoplastic resin, polyphenylene sulfide (PPS), polybutylene terephthalate (PBT), etc. can be used. The composition containing the thermoplastic resin may contain the above-mentioned filler and the like in addition to the thermoplastic resin.

[0109] [Example]

[0110] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0111] 《Examples 1 to 12》

[0112] Make it as follows Figure 1 The electrolytic capacitor 1 shown was used to evaluate its characteristics.

[0113] (1) Fabrication of capacitor elements

[0114] An aluminum foil (thickness 100 μm) was prepared as a substrate, and the surface of the aluminum foil was etched to obtain an anode body 6. The anode body 6 was immersed in a phosphoric acid solution (liquid temperature 70° C.) with a concentration of 0.3 mass % and a DC voltage of 70 V was applied for 20 minutes to form a dielectric layer 7 containing aluminum oxide (Al2O3) on the surface of the anode body 6. Thereafter, an insulating anti-corrosion tape (separation layer 13) was attached to a predetermined portion of the anode body 6.

[0115] An aqueous solution containing pyrrole monomer and p-toluenesulfonic acid was prepared. The monomer concentration in the aqueous solution was 0.5 mol / L, and the p-toluenesulfonic acid concentration was set to 0.3 mol / L. The anode body 6 and the counter electrode formed with the dielectric layer 7 were immersed in the obtained aqueous solution, and electrolytic polymerization was performed at 25° C. and a polymerization voltage of 3 V to form a solid electrolyte layer 9.

[0116] A dispersion (carbon paste) obtained by dispersing flaky natural graphite and the first polymer shown in Table 1 in water was applied to the solid electrolyte layer 9 and then heated at 200° C. to form a carbon layer 11 on the surface of the solid electrolyte layer. The ratio of graphite particles to the carbon paste was 5% by mass.

[0117] Next, a silver paste containing silver particles and a binder resin (epoxy resin) is applied to the surface of the carbon layer 11, and then heated to cure the binder resin to form the silver paste layer 12. In this way, the cathode extraction layer 10 composed of the carbon layer 11 and the silver paste layer 12 is formed.

[0118] As described above, a plurality of capacitor elements 2 having carbon layers with different compositions were obtained.

[0119] (2) Assembly of electrolytic capacitors

[0120] Furthermore, anode lead terminal 4 , cathode lead terminal 5 , and adhesive layer 14 were disposed on capacitor element 2 , and outer casing 3 was formed using a resin containing silica particles as a filler, thereby producing an electrolytic capacitor.

[0121] 《Examples 13 to 19》

[0122] In the preparation of the carbon paste, in addition to the first polymer shown in Table 1, 6 parts by mass of the second polymer shown in Table 1 was added to 100 parts by mass of the carbon material to obtain a carbon paste. Electrolytic capacitors were prepared in the same manner as in Examples 1 to 12 except for the above.

[0123] 《Examples 20-22》

[0124] In the preparation of the carbon paste, in addition to the first polymer shown in Table 1, the second polymer was added in the mass parts shown in Table 1 relative to 100 parts by mass of the carbon material to obtain a carbon paste. Except for this, the same operation as in Example 13 was carried out to produce an electrolytic capacitor.

[0125] 《Comparative Examples 1 and 2》

[0126] In the preparation of the carbon paste, p-phenolsulfonic acid or p-toluenesulfonic acid was added as a low molecular weight additive instead of the first polymer to obtain a carbon paste. Except for this, the same operation as in Example 1 was carried out to produce an electrolytic capacitor.

[0127] 《Comparative Examples 3 and 4》

[0128] In the preparation of the carbon paste, carboxymethyl cellulose (weight average molecular weight 100,000) was added in place of the first polymer at the ratio shown in Table 1 to obtain a carbon paste. Electrolytic capacitors were prepared in the same manner as in Examples 1 to 12 except for the above.

[0129] Table 1 shows the content of additives (first and second polymers, or low molecular additives) in the carbon paste for the electrolytic capacitors of Examples 1 to 22 and Comparative Examples 1 and 2. In Table 1, the content of the first and second polymers is expressed in parts by mass relative to 100 parts by mass of the carbon material. In addition, Table 1 also shows the molecular weight (weight average molecular weight) of the first and second polymers, and the amount of acid groups introduced into the first and second polymers (the number of acid groups per 100 monomers corresponding to the repeating units of the first and second polymers). In Table 1, the electrolytic capacitors of Examples 1 to 22 are A1 to A22, respectively. The electrolytic capacitors of Comparative Examples 1 and 2 are B1 and B2, respectively. It should be noted that in Examples 13 to 18, 20 to 22 and Comparative Examples 3 and 4, ammonium salt of carboxymethyl cellulose is used, and carboxymethyl cellulose having 30 acid groups (carboxyl groups) per 100 monomers is used.

[0130] The electrolytic capacitors of Examples and Comparative Examples produced above were evaluated as follows.

[0131] [evaluate]

[0132] The ESR value (mΩ) of the electrolytic capacitor at a frequency of 100 kHz was measured using a 4-terminal LCR meter in an environment of 20° C. as an initial ESR value (X0) (mΩ).

[0133] Next, the electrolytic capacitor was placed in an environment at 125° C. for 1000 hours. The ESR value (X1) (mΩ) of the electrolytic capacitor after 1000 hours was measured in the same manner as above. Then, the rate of change of ESR was calculated using the following formula.

[0134] ESR change rate = X1 / X0

[0135] The evaluation results are shown in Table 2. In Table 2, the initial ESR is shown as a relative value with the initial ESR of the electrolytic capacitor B1 of Comparative Example 1 being 100.

[0136] [Table 1]

[0137]

[0138] [Table 2]

[0139] Initial ESR ESR change rate A1 85 1.5 A2 94 2.1 A3 88 1.8 A4 87 2.1 A5 85 1.5 A6 85 1.5 A7 87 1.7 A8 85 1.5 A9 87 1.4 A10 91 1.6 A11 87 1.5 A12 84 2.8 A13 86 1.3 A14 86 1.3 A15 86 1.7 A16 83 2.4 A17 85 2 A18 86 1.5 A19 89 1.6 A20 85 1.5 A21 86 1.4 A22 88 1.3 B1 100 5.8 B2 102 7.8 B3 100 26 B4 103 20

[0140] Industrial Applicability

[0141] The electrolytic capacitor of the present invention can suppress the deterioration of the conductive polymer contained in the solid electrolyte layer and suppress the increase of ESR even when exposed to a high temperature atmosphere or a high humidity atmosphere. Therefore, it can be used in various applications requiring low ESR.

[0142] Description of Reference Numerals

[0143] 1: electrolytic capacitor, 2: capacitor element, 3: outer casing, 4: anode lead terminal, 5: cathode lead terminal, 6: anode body, 7: dielectric layer, 8: cathode part, 9: solid electrolyte layer, 10: cathode lead layer, 11: carbon layer, 12: silver paste layer, 13: separation layer, 14: adhesive layer.

Claims

1. An electrolytic capacitor comprising a capacitor element, the capacitor element comprising an anode body, a dielectric layer covering at least a portion of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a cathode lead layer covering at least a portion of the solid electrolyte layer, The cathode extraction layer includes a carbon material, a first polymer having an acid group, and a second polymer having a water solubility different from that of the first polymer. The acid group includes at least one selected from a sulfonic group and a derivative of a sulfonic group, The second polymer is a cellulose-based polymer and / or polyvinyl alcohol, The content of the first polymer is 1 part by mass or more relative to 100 parts by mass of the carbon material.

2. The electrolytic capacitor according to claim 1, wherein: The acid group is introduced into the monomer corresponding to the repeating unit of the first polymer, The number of the acid groups is 50 or more per 100 of the monomers.

3. The electrolytic capacitor according to claim 1 or 2, wherein: The content of the first polymer is 1 part by mass or more and 5000 parts by mass or less relative to 100 parts by mass of the carbon material.

4. The electrolytic capacitor according to claim 1 or 2, wherein: The weight average molecular weight of the first polymer is 2,000 or more and 1,000,000 or less.

5. The electrolytic capacitor according to claim 1 or 2, wherein: The second polymer includes a cellulose-based polymer.

6. The electrolytic capacitor according to claim 1 or 2, wherein: The second polymer includes polyvinyl alcohol.

7. The electrolytic capacitor according to claim 1 or 2, wherein: The content of the second polymer is 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the first polymer.

8. The electrolytic capacitor according to claim 1 or 2, wherein: The cathode lead layer includes a first conductive layer covering at least a portion of the solid electrolyte layer, and a second conductive layer covering at least a portion of the first conductive layer. The first conductive layer includes the first polymer.

Citation Information

Patent Citations

  • Solid electrolytic capacitor

    JP2008027998A

  • Manufacturing method of solid electrolytic capacitor and solid electrolytic capacitor

    JP2012069789A

  • Method of fabricating solid electrolytic capacitor and solid electrolytic capacitor

    US20120075774A1